PREVALENCE OF LONG QT SYNDROME AND OTHER CARDIAC DEFECTS IN DEAF-MUTE CHILDREN - Niaz, Ahsan; Rizvi, Syed Faiz-ul-hassan; Khurram, Daniyeh (Journal of Ayub Medical College Abbottabad, 2011)
Background: Long QT syndrome is considered a fatal disease because of its association with ventricular arrhythmias and sudden cardiac death. Objectives of study were to determine the prevalence of long QT syndrome and other heart diseases, in deaf-mute children. Methods: A Cross-sectional descriptive study was conducted at Cholistan special education centre and Cardiology department, Sheikh Zayed hospital Rahim Yar Khan, Pakistan in September 2006. A total of 104 congenitally deafmute children were assessed. Height, weight and blood pressure measured, 12-lead electrocardiogram done and QTc calculated using Bazette’s formula. Children with prolonged QTc underwent 24-hour ambulatory ECG recording. All were auscultated following complete protocol. A child with murmur was further evaluated with colour Doppler echocardiography. Audiometry was performed on all the children and the result interpreted according to WHO recommendations. Diagnosis of LQTS was based on Revised Schwartz criteria. Results: Out of 104 children, 62 were male with mean age 11.89 yrs. The average systolic and diastolic BP was 97/67 mmHg. Average height was 126 Cm. All children had moderate to severe bilateral sensorineural hearing loss (40-80 dB). One child had associated Patent Ductus Arteriosis. Fifteen had an innocent murmur. Prevalence of congenital heart disease was found to be 0.1/1000. Four children had QT interval more than 440 mSec, (range 0.46-0.47 mSec.). Both genders were equally affected. Three children had high probability of LQTS and one had intermediate probability. Screening of family of these 4 patients showed prolonged QT interval in the sibling of one patient. Conclusion: Our study highlights the significant prevalence of Jervell Lange-Nielsen Syndrome in Pakistani deaf-mute children, which may be associated to the high level of consanguinity in this region. Awareness of this syndrome among health care providers is needed as timely diagnosis and subsequent treatment may prevent fatal complications. Keywords: Long QT Syndrome, Deafness, Congenital Heart Defects